The Moderating Role of Return on Assets on Sharia Stock Returns: A Case Study on the Jakarta Islamic Index - Hendri Hermawan Adinugraha (Institut Agama Islam Negeri Kendari, 2021)
This research aims to analyze the impact of Debt to Equity Ratio (DER), Exchange Value, and Index ISR in Sharia Stock Return pass of Return on Asset (ROA) in a company administered in the Jakarta Islamic Index 2013-2017 period. This sample choosing with the purposive sampling method with the total sample as 29 from 30 companies. The data used in this study is the secondary data, and data analysis used is the multiple linear regression analysis and path analysis. The research result indicates that experiment T Debt to Equity Ratio (DER) and Index ISR are not influential in Stock Return. Exchange Value and Return on Asset (ROA) significance of Stock Return. Debt to Equity Ratio (DER) and Index ISR influence Return on Asset (ROA). At the same time, Exchange Value is not influential with Return on Asset. Experiment F refers that DER, Exchange Value, and Index ISR influence Return on Asset and Stock Return. However, ROA cannot mediate the relation between DER, Exchange Value, and Index ISR in Stock Return.